Microglia Polarization From M1 to M2 in Neurodegenerative Diseases - Guo, Shenrui; Wang, Hui; Yin, Yafu (Frontiers in Aging Neuroscience, 2022)
Microglia-mediated neuroinflammation is a common feature of neurodegenerative diseases such as Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS) and multiple sclerosis (MS). Microglia can be categorized into two opposite types: classical (M1) or alternative (M2), though there’s a continuum of different intermediate phenotypes between M1 and M2, and microglia can transit from one phenotype to another. M1 microglia release inflammatory mediators and induce inflammation and neurotoxicity, while M2 microglia release anti-inflammatory mediators and induce anti-inflammatory and neuroprotectivity. Microglia-mediated neuroinflammation is considered as a double-edged sword, performing both harmful and helpful effects in neurodegenerative diseases. Previous studies showed that balancing microglia M1/M2 polarization had a promising therapeutic prospect in neurodegenerative diseases. We suggest that shifting microglia from M1 to M2 may be significative and we focus on the modulation of microglia polarization from M1 to M2, especially by important signal pathways, in neurodegenerative diseases.